Comparison of Government Efforts in Improving the Welfare of Indonesian Workers Based on Law Number 13 of 2003 concerning Manpower and Draft Law Number 11 of 2020 concerning Job Creation - Surya Perdana (International Journal Reglement & Society (IJRS), 2021)
Manpower can be defined as everything related to labor and the time before, during and after the work period. When talking about various labor issues, this can be viewed from various factors and meanings. Due to the fact that the labor factor is a human resource, during the current national development period, it is a very important factor for the course of national development in Indonesia. The Manpower Act was created, of course, to provide welfare to workers, especially Indonesian workers. In 2020 the government will carry out a policy by drafting a new law on labor through the omnimbus law. Of course, the basic needs of every human being will continue to exist and develop according to the stages or stages of the human life cycle. The procedure used to collect data in this study is documentation, namely the guidelines used in the form of notes or quotes, search for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. Comparisons related to the protection of labor welfare in Indonesia based on UUK and UUCK if it is concluded that there are several differences, for example regarding weekly breaks, the UUK regulates weekly rest periods of 2 days off in 5 working days while UUCK only regulates 1 day off within 6 working days incidentally it has also been regulated in the UUK. While the right to take a long break in the UUK is given at least 2 months and can be implemented in the seventh or eighth year of 1 month each, while the UUCK does not include the right to long leave and submit the rules for long leave to the respective companies or cooperation agreements that agreed upon. Regarding menstrual leave for female workers in the UUK, they can get a day off on the first and second days, whereas in UUCK it is not regulated. Furthermore, in the UUK it regulates severance pay while in the UUCK it is not regulated and in the UUK it regulates the work period reward money, workers who have worked 24 years or more are given 10 months of wages but this rule is abolished in UUCK. Pension security is regulated in the UUK but not in the UUCK. Meanwhile, job loss insurance is not regulated in the UUK but in UUCK adds a new social security program, namely Job Loss Security (JKP) which is managed by BPJS. Regarding the work status in UUK is regulated in Article 59 then that Article Article is deleted by UUCK, with the removal of this article, there is no limit to the rules that a worker can be contracted, as a result the worker could become a lifelong contract worker. In UUK, the maximum overtime work is only 3 hours per day in 14 hours per week, while in UUCK the maximum is 4 hours per day and 18 hours per week